Slow excitatory synaptic potentials recorded from neurones of guinea-pig submucous plexus. - Surprenant, A (1984)
Intracellular recordings made from neurones of guinea-pig submucous plexus revealed three types of synaptic input: cholinergic excitatory synaptic potentials (fast e.p.s.p.s) of 50-80 ms duration, inhibitory synaptic potentials (i.p.s.p.s) of 1 s duration, and non-cholinergic, non-adrenergic slow e.p.s.p.s which lasted for 15-20 s. A single stimulus was sufficient to elicit the slow e.p.s.p. in all neurones in which this synaptic input was present. Slow e.p.s.p.s were recorded in those neurones which also displayed i.p.s.p.s. Both the i.p.s.p. and the slow e.p.s.p. appeared in an all-or-none fashion and were not affected by alterations in the stimulus strength. The inhibitory as well as the slow excitatory synaptic potentials reversed close to the K+ equilibrium potential, indicating that the i.p.s.p. is due to an activation of K+ conductance while the slow e.p.s.p. is due to its inactivation. Evidence is presented which suggests the slow e.p.s.p. may be generated at a synapse located some distance from the soma, presumably at a dendritic location. Only those cells which showed slow e.p.s.p.s responded to substance P with a depolarization which mimicked the slow e.p.s.p.